Turkish Domestic Actors’ Role in Foreign Policy Making: Case of Turkey – KRG’s Strategic Bilateral Partnership - L, Luerdi (Global: Jurnal Politik Internasional, 2019)
This paper aims to describe the role of Turkish domestic societal actors in the state policy making in the case of strategic bilateral partnership between Turkey and the Kurdistan Regional Government (KRG); a quasi state within the Iraqi federal state. The rareness of literature describing domestic forces within Turkey and the consequence for the state’s policy in building a strategic partnership with the KRG was the gap that this research would be expected to narrow. The paper argues that Turkish domestic actors like the individual, the Justice and Development Party (AKP), the Turkish military and business people had an important role; shaping Turkey’s preference and national interests strongly determined by their views on nation and economic regulation which occupied its legitimate preference. The research applied the ideational liberal theory proposed by Andrew Moravcsik emphasizing the primacy of domestic actors. The research was qualitative with descriptive analysis model. The paper represents a perspective that identity or values well embedded in domestic actors’ views do matter to understand the state behavior either cooperation or conflict.